A Study on customer satisfaction towards services provided by MITI Sabah Branch / Roslina Mappahli - Mappahli, Roslina (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2006)
MITI stand for Ministry of International Trade and Industry Malaysia. It is government sector, where by responsible in economic sector. MITl's customers are exporter and importer, which all of them dealing with MITI to trade their product to foreign countries. Descriptive Study based on the survey of MITl's customer, about their level of satisfaction towards the services provided by MITI. Its main objectives are to find out the level of services performed. Secondly, to see if the MITI service can fulfill the customer needs and lastly, to know which services needed to be improved. Statistical Package of Social Science (SPSS) software was used to produce the intended result at findings of the study. A sample size of 150 respondents chosen via judgmental sampling was fundamental in generating the required inputs. The study has discovered that most of customers are satisfied with MITl's services. All the objectives of the research were answered; few recommendation and suggestion are also put forward to improve the present customer service and any related factors for the maximization of customer satisfaction.